Microstructure evolution and mechanical properties of γ-TiAl honeycomb structure fabricated by isothermal forging and pulse current assisted diffusion bonding. (August 2018) - Shi, Chengcheng; Lu, Zhen; Zhang, Kaifeng; Deng, Linwei; Wang, Cheng
Abstract: The hot deformation behavior and pulse current assisted diffusion bonding (PCDB) behavior of sintered γ-TiAl based alloy with near gamma microstructure were investigated for fabricating honeycomb structure via isothermal forging - PCDB route. Honeycomb core structures were fabricated via isothermal forging at 1150–1250 °C with a nominal strain rate of 10 −3 s −1 based on the hot deformation behavior of the sintered alloy. Additionally, the mechanical property and structural morphology demonstrated that the best forging parameter was forging at 1200 °C with a nominal strain rate of 10 −3 s −1 . Subsequently, the effects of bonding temperature, holding time, and bonding pressure on the microstructure evolution, plastic strain, and shear strength of the PCDB joints were investigated. The plastic strain and shear strength of the PCDB joints increased with increasing bonding temperature, time and stress, additionally, the fracture mode transformed from interfacial sliding fracture into substrate fracture with the optimization of bonding parameters. Furthermore, a sound metallurgical bonding joint with smaller plastic strain and shear strength as high as 92% of the base material was achieved at 1100 °C with a holding time of 20 min and a pressure of 25 MPa, showing priority compared to traditional hot pressing diffusion bonding process. Highlights: Hot deformation behavior of hot pressing sintered TiAl alloy was investigate. Honeycomb core structure of TiAl alloy was fabricated via isothermal forging. Pulse current assisted diffusion bonding of TiAl alloy was investigated.